Optimalisasi Rute Distribusi Bayam Hijau Di PT Sayuran Pagi - Irfansyah Dwi S; Maura Putri Nur Afifah; Queen Dzakyla M (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2024)
PT Sayuran Pagi is a company that operates in the agricultural sector and focuses on hydroponic vegetables such as spinach, kale, curly kale and other types of vegetables, and is located in the city of Depok and is a Limited Liability Company (PT). The Morning Vegetable Company has three gardens which are used, one of which is the Cipaku area, Bogor, where all of its production will be sent first to a warehouse in Depok and then distributed to several partners who have collaborated. The increase in consumption of green spinach among the public affects the distribution of this vegetable, which means companies must be able to meet demand with proper distribution. In this research, to determine the shortest route when distributing from the garden to the warehouse using the Dijkstra algorithm. Based on the calculation results, the optimal solution for the shortest route is route A-C-B-F-H-I or from the toll road with a total distance of 10.55km. However, because the focus of this research is on costs, from the results of the research using the Dijkstra algorithm calculation method, it can be concluded that PT. Sayuran Pagi can take the non-toll route because the costs incurred are less than the toll route.